Effect of Repetitive Transcranial Magnetic Stimulation (rTMS) in Post-Stroke Lower Limb Motor Recovery: A Systematic Review - Risca Hijrianti; Andriani Purwaningrum; Haryo Teguh (The International Journal of Medical Science and Health Research, 2025)
Introduction : Transcranial magnetic stimulation (TMS) is a non-invasive technique that offers potential for enhancing motor function recovery after stroke by modulating brain activity. Among the different forms of TMS, repetitive TMS (rTMS) has been identified as a promising tool for stimulating brain regions associated with lower limb movement and improving motor function. This review aimed at assessing the effect of in rTMS in post-stroke lower limb motor recovery Methodology : This systematic review followed PRISMA guidelines and included randomized controlled trials examining the effects of rTMS on lower limb motor recovery in post-stroke patients. Eligible studies involved adult stroke patients with motor dysfunction, and interventions included rTMS alone or combined with rehabilitation or medication therapy. The primary outcome assessed was motor function, with various measurement tools used. A comprehensive literature search was conducted across multiple databases, and data extraction and quality assessment were done independently by the authors using the Modified Jadad Scale. Results : A total of 14 randomized controlled studies were included in this review, involving 277 participants with varying stroke types and severities. The studies assessed the effects of low- frequency (1 Hz) and high-frequency (5-20 Hz) rTMS, combined with rehabilitation therapies, on lower limb motor recovery. The results showed significant improvements in lower limb motor function, balance, and spasticity, particularly with both high or low-frequency rTMS combined with other rehabilitation therapies. High-frequency rTMS also yielded positive effects, particularly in walking speed and gait symmetry. Conclusion : The rTMS procedure consistently showed improvements in lower motor function, balance, and gait in post-stroke patients compared to sham and control interventions.